BCG vaccine may generate cross-reactive T cells against SARS-CoV-2: In silico analyses and a hypothesis. Issue 41 (22nd September 2020) - Tomita, Yusuke; Sato, Ryo; Ikeda, Tokunori; Sakagami, Takuro
Highlights: BCG contains similar 9-amino acid sequences with SARS-CoV-2. The peptides have moderate to high binding affinity to common HLA class I molecules. Cross-reactive T cells against SARS-CoV-2 could be generated by BCG vaccination. Abstract: The world is facing the rising emergency of SARS-CoV-2. The outbreak of COVID-19 has caused a global public health and economic crisis. Recent epidemiological studies have shown that a possible association of BCG vaccination program with decreased COVID-19-related risks, suggesting that BCG may provide protection against COVID-19. Non-specific protection against viral infections is considered as a main mechanism of BCG and clinical trials to determine whether BCG vaccine can protect healthcare workers from the COVID-19 are currently underway. We hypothesized that BCG may carry similar T cell epitopes with SARS-CoV-2 and evaluated the hypothesis by utilizing publicly available database and computer algorithms predicting human leukocyte antigen (HLA) class I‐binding peptides. We found that BCG contains similar 9-amino acid sequences with SARS-CoV-2. These closely-related peptides had moderate to high binding affinity for multiple common HLA class I molecules, suggesting that cross-reactive T cells against SARS-CoV-2 could be generated by BCG vaccination.